Copper alloy material for automobile wire harness terminal and preparation method of copper alloy material
By optimizing the formulation and process of copper alloy materials, using horizontal continuous casting and electromagnetic casting processes, combining homogenized annealing and solid solution treatment, the problems of low yield and complex process of existing copper alloy materials for automotive wire harness terminals have been solved, and the problem of low yield and complex process is achieved. Efficient and economical production and improve the overall performance of materials.
Patent Information
- Application Number
- CN202411508292.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
AI Technical Summary
The existing copper alloy materials for automotive wiring harness terminals have low yields, easy to produce waste, and complex production processes, high investment costs for equipment and long production cycles.
The formula of copper alloy material contains 0.5-1.2% Ni, 1-2.2% Sn, 0.01-0.3% P, 0.1-0.8% Zn, 0.01-0.02% Mg and 0.01-0.5% Si, At least two elements of Cr, Zr, Mn and Ag are optimized to improve material performance by horizontal continuous casting process and electromagnetic casting, combining homogenized annealing and solid solution treatment, finishing rolling and aging treatment.
The high conductivity, high strength and high bending processability of copper alloy materials are achieved, the yield rate is improved, the waste generation is reduced, the process flow is simplified, the production cost is reduced, and the overall performance of the material is improved.
Smart Images

Figure BDA0005104671370000171 
Figure BDA0005104671370000181
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy processing, and in particular to a copper alloy material for automobile wiring harness terminals and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of China's automobile industry, the development of automobile parts including automobile connectors has been greatly promoted. Automobile connectors are one of the important basic components in electronic systems that are responsible for power transmission, signal control and transmission. They are mainly composed of plug-ins (terminals), insulators, shells and accessories. Terminals are the core components to realize the internal electrical contact function of connectors. The raw materials used for connector terminals are mainly copper alloys. The quality of the materials of connector terminals is related to the quality and reliability of connectors. The materials of connector terminals should not only be considered from the mechanical properties, thermodynamic properties, electrical properties and electrochemical corrosion properties, but also from the aspects of material machinability and cost. At present, the copper materials for terminal connectors are mainly prepared by the following methods: semi-continuous casting → ingot heating → hot rolling → online solution quenching → milling → rough rolling → annealing → finishing rolling → annealing → finished product rolling → finished product packaging. This method has many and complex processes, a long production cycle, and requires a large number of special equipment. The equipment investment cost is high. Secondly, due to the complexity of the process, it is easy to produce waste, resulting in a low yield.
[0003] Based on this, a new copper alloy material is urgently needed to overcome the above-mentioned problems and shortcomings. Summary of the invention
[0004] In view of this, the present invention proposes a copper alloy material for automobile wiring harness terminals to solve the problem of low yield and easy generation of waste products in the prior art of automobile wiring harness terminals.
[0005] To solve the above problems, the present invention provides a copper alloy material for automobile wiring harness terminals, which comprises, by mass percentage, 0.5-1.2% Ni, 1-2.2% Sn, 0.01-0.3% P, 0.1-0.8% Zn, 0.01-0.02% Mg, and 0.01-0.5% of at least two elements selected from Si, Cr, Zr, Mn and Ag, with the remainder being Cu and unavoidable impurities.
[0006] In some embodiments, the Si content is 0.05-0.2%, and / or; the Cr content is 0.005-0.05%, and / or; the Zr content is 0.005-0.05%, and / or; the Mn content is 0.005-0.3%, and / or; the Ag content is 0.005-0.01%.
[0007] Another aspect of the present invention provides a method for preparing the above copper alloy material for automobile wiring harness terminals, comprising the following steps:
[0008] Step 1, preparing raw materials according to the composition of the copper alloy material for automobile wiring harness terminals, the raw materials comprising: electrolytic copper, CuNi master alloy, CuP master alloy, CuMg master alloy, pure Zn, pure Sn and a first raw material, the first raw material being selected from at least two of CuSi master alloy, CuCr master alloy, CuZr master alloy, CuMn master alloy and CuAg master alloy;
[0009] Step 2, smelting and keeping the electrolytic copper in a melting furnace, and sequentially adding pure Zn, pure Sn and CuNi master alloy, CuP master alloy, CuMg master alloy and the first raw material to obtain an intermediate solution;
[0010] Step 3: The intermediate solution is subjected to a second heat preservation, and then passed through a submerged flow trough converter to a heat preservation furnace. After the solution composition meets the casting requirements, the third heat preservation is carried out, and then electromagnetic horizontal continuous casting is carried out at a casting temperature of 1150-1160° C. to obtain a coil blank;
[0011] Step 4: homogenizing annealing the coiled blank, then double-sided milling, and finally cold rough rolling with a cold rough rolling thickness of 1.0-1.5 mm, and then solution treatment to obtain a solution quenched blank;
[0012] Step 5, subjecting the solution quenched billet to finish rolling deformation, with a finishing rolling deformation amount of 40-60%, and then subjecting the billet to an aging treatment to obtain a primary aging billet;
[0013] Step 6: Roll the primary aging billet into finished product, and then perform secondary aging treatment to obtain a finished strip.
[0014] In some embodiments, in step 2, the smelting temperature is 1220-1240°C, and the holding temperature is 1200-1220°C.
[0015] In some embodiments, in step three, the second insulation temperature is 1180-1200° C., and the insulation time is 8-10 min, and / or; the third insulation temperature is 1160-1180° C., and the insulation time is 2-5 min.
[0016] In some embodiments, in step three, the electromagnetic casting process has a frequency of 20-40 Hz and a current of 20-30A.
[0017] In some embodiments, in step three, the process parameters of horizontal continuous casting are: casting speed is 160-190 mm / min, pulling speed is 16-20 mm / s, pause time is 1-3s, and withdrawal speed is 6-8 mm / s.
[0018] In some embodiments, in step 4, the homogenization annealing temperature is 700-750° C., the holding time is 4-6 hours, the solution treatment temperature is 880-900° C., and the holding time is 2-5 minutes.
[0019] In some embodiments, in step five, the primary aging temperature is 500-530° C., and the holding time is 4-6 hours.
[0020] In some embodiments, in step five, the rolling deformation of the finished product is 45-55%, the temperature of the secondary aging treatment is 420-450° C., and the holding time is 4-6 hours.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] This application controls the content of Ni, Sn, P, Zn, Mg, Si, Cr, Zr, Mn and Ag in the copper alloy material for automobile wiring harness terminals within a specific range, and through the synergistic effect of these alloy elements, the balance of high conductivity, high strength and high bending processability of the alloy is achieved; and through a short-process horizontal continuous casting process, and assisted by electromagnetic casting, a copper material with uniform organization and controllable composition can be prepared, effectively improving the problem of uneven composition; at the same time, through solution quenching, by controlling the grain size and the distribution and size of the precipitated phase, the synergistic control of conductivity, strength and bending processability is achieved, which is convenient for its application needs in the fields of automotive electronic connectors, sensors, relays, controllers, etc. Compared with the existing methods, this method has the characteristics of simple operation, short process flow, high yield rate, strong market competitiveness and significant economic benefits. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.
[0025] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.
[0026] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.
[0027] In the production process of existing copper materials for automotive connectors, semi-continuous casting is mostly used. However, semi-continuous casting involves multiple complex process steps, including ingot heating, hot rolling, online solution quenching, milling, rough rolling, annealing, finishing rolling, etc. The process is long, energy consumption is high, and the product yield is low. The use of process steps can shorten the entire casting process, shorten the process, and can achieve continuous casting, reduce downtime, and improve production efficiency. At the same time, the heating and hot rolling of copper ingots are reduced, which can save energy. At the same time, horizontal continuous casting can better control the cooling rate of horizontal continuous casting ingots, reduce internal and surface defects, and improve the internal quality and surface quality of copper ingots. Since continuous production reduces the cutting of heads and tails of copper ingots, the metal recovery rate is improved.
[0028] In order to solve the above-mentioned shortcomings, the inventors decided to adopt the horizontal continuous casting method to prepare copper alloy materials for automotive wiring harness terminals, and at the same time optimized the material formula of the alloy. Specifically, calculated by mass percentage as 100%, the copper alloy material includes: 0.5-1.2% Ni, 1-2.2% Sn, 0.01-0.3% P, 0.1-0.8% Zn, 0.01-0.02% Mg and 0.01-0.5% of at least two elements of Si, Cr, Zr, Mn and Ag, and the balance is Cu and unavoidable impurities.
[0029] By adding a proper amount of Ni, the strength and corrosion resistance of the copper material are increased. Preferably, the content of Ni is 0.1-1.2wt%.
[0030] Adding a proper amount of Sn can improve the mechanical properties and electrical conductivity of the copper material. Preferably, the content of Sn is 1.0-2.2wt%.
[0031] Adding a proper amount of P can improve the wear resistance and strength of the copper material. Preferably, the content of P is 0.01-0.3wt%.
[0032] Adding a proper amount of Zn can increase the oxidation resistance of the copper material and improve the processability. Preferably, the Zn content is 0.1-0.8wt%.
[0033] Adding a proper amount of Mg refines the grains and improves the comprehensive properties of the material. Preferably, the Mg content is 0.01-0.02wt%.
[0034] And appropriate amounts of any two or more elements of Si, Cr, Zr, Mn and Ag further improve the strength, corrosion resistance and conductivity of the copper material. Preferably, the total content of these elements is 0.01-0.5wt%.
[0035] Preferably, the Si content is 0.05-0.2%, and / or; the Cr content is 0.005-0.05%, and / or; the Zr content is 0.005-0.05%, and / or; the Mn content is 0.005-0.3%, and / or; the Ag content is 0.005-0.01%.
[0036] Si can form a strengthening phase, improve the strength and hardness of copper alloys, while maintaining good conductivity. The right amount of silicon can also improve casting performance and wear resistance.
[0037] Cr in copper alloys can improve the corrosion resistance of materials, especially in high temperature and corrosive environments. Cr can also refine the grains and further improve the mechanical properties of the materials.
[0038] Zr can refine the grain structure in copper alloys and improve the strength and toughness of the material. Zirconium can also form stable compounds with other alloy elements to improve the thermal stability and creep resistance of the material.
[0039] Mn can form a solid solution with copper to improve the hardness and strength of the material. Manganese can also enhance the wear resistance and impact resistance of copper alloys while maintaining good processing performance.
[0040] Ag is a highly conductive element, and a small amount of silver addition can significantly improve the conductivity of copper alloys. Silver can also enhance the material's anti-oxidation and corrosion resistance, especially in high temperature environments.
[0041] By precisely controlling the content of trace elements such as Si, Cr, Zr, Mn, and Ag, the comprehensive properties of copper alloys can be significantly improved, making them more suitable for the production of automotive connectors. Specifically, the effects of these trace elements include improving mechanical strength and hardness, enhancing conductivity and corrosion resistance, refining grain structure, and optimizing processing performance. These improvement measures can effectively overcome the inherent deficiencies of the horizontal continuous casting process and ensure the production of high-quality automotive connector copper materials.
[0042] At the same time, the inventors optimized the process of horizontal continuous casting, wherein:
[0043] In step 2, the melting and heat preservation are carried out according to the formula to ensure the uniformity and purity of the materials. The order of addition is strictly controlled to ensure that all elements are fully melted to form a uniform intermediate melt, avoiding air absorption and oxidation burning. The submerged flow launder converter is used to reduce the time the melt is exposed to the air and reduce the possibility of oxidation and impurity introduction. The heat preservation furnace further stabilizes the melt composition and temperature.
[0044] In step three, the crystal structure control problem of horizontal continuous casting is solved by precisely controlling the process parameters of electromagnetic horizontal continuous casting. The optimized casting and drawing speeds ensure that the copper material is uniformly crystallized during the cooling process, reducing grain unevenness and internal stress. Reasonable pauses and withdrawal speeds control the cooling speed, break the grains, form more nucleation points, and avoid defects caused by too fast or too slow cooling.
[0045] In step 4, homogenization annealing and solution treatment are performed to further improve the microstructure and performance of the material. Long-term annealing at a higher temperature eliminates the segregation and uneven structure formed during the casting process and homogenizes the composition and grain structure of the material. High-temperature and short-time solution treatment can effectively control the uniformity and size of the material's structure, and can effectively dissolve the alloy elements into the matrix, which is convenient for subsequent aging precipitation and ensures the feasibility of subsequent processing.
[0046] In steps five and six, finishing rolling and aging treatment are performed to ensure the performance of the final product. Finishing rolling improves the strength of the material, provides limited deformation energy storage for subsequent aging, and ensures the stability of the material in use. Aging treatment improves the strength and hardness of the material, and further optimizes the mechanical and electrical properties.
[0047] The technical solution proposed in this application improves the strength, conductivity, corrosion resistance and processing performance of the material by adding specific alloy elements. The smelting and insulation processes are optimized to reduce oxidation and the introduction of impurities, ensuring the purity and uniformity of the material. In the electromagnetic horizontal continuous casting process, the casting speed, drawing speed, pause time and withdrawal speed are precisely controlled to ensure a fine and uniform crystalline structure and cooling. Through homogenization annealing and solution treatment, casting defects are eliminated, the composition and grain structure are homogenized, and the comprehensive performance of the material is improved. Finishing rolling and aging treatment further optimize the material properties and ensure the quality of the final product. Through the above-mentioned optimization measures, the problems of low production efficiency and low yield of automotive wiring harness terminals in the prior art can be effectively overcome, while the quality of the connector terminal copper material is improved.
[0048] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0049] Example 1
[0050] The composition of the copper alloy material for the automotive wiring harness terminal of this embodiment is shown in Table 1 and Table 2, and the performance test results are shown in Table 3, which are as follows:
[0051] S1. Prepare raw materials according to the composition of the copper alloy material for automobile wiring harness terminals, wherein the raw materials include: electrolytic copper, CuNi master alloy, CuP master alloy, CuMg master alloy, pure Zn, pure Sn and a first raw material, wherein the first raw material is selected from at least two of CuSi master alloy, CuCr master alloy, CuZr master alloy, CuMn master alloy and CuAg master alloy;
[0052] S2, smelting and heat-insulating the electrolytic copper in a melting furnace, the smelting temperature is 1230° C., the heat-insulating temperature is 1215° C., pure Zn, pure Sn and CuNi master alloy, CuP master alloy, CuMg master alloy and the first raw material are added in sequence, sampling and analyzing the qualified products, and obtaining an intermediate solution;
[0053] S3, the intermediate solution is subjected to a second insulation, the second insulation temperature is 1195°C, the insulation time is 8min, and the intermediate solution is transferred to the insulation furnace through the submerged flow trough converter. After the solution composition meets the requirements of the pulling column, the third insulation is carried out, the third insulation temperature is 1175°C, the insulation time is 3min, and then electromagnetic horizontal continuous casting is carried out. The electromagnetic casting process is 30HZ frequency, 20A current, casting temperature 1160°C, drawing speed 160mm / min, drawing speed 16mm / s, pause time 1s, and withdrawal speed 6mm / s to obtain a coil blank;
[0054] S4, homogenizing annealing the coiled blank at a temperature of 720°C and a holding time of 5 hours, then double-sided milling, and finally cold rough rolling with a cold rough rolling thickness of 1.5 mm, and then solution treatment at a temperature of 880°C and a holding time of 5 minutes to obtain a solution quenched blank;
[0055] S5, subjecting the solution quenched billet to finish rolling deformation, with a finishing rolling deformation of 60%, and then subjecting it to primary aging treatment, with a primary aging temperature of 500° C. and a holding time of 6 h, to obtain a primary aging billet;
[0056] S6. The primary aging billet is subjected to finished product rolling, and the finished product rolling deformation is 45%, followed by secondary aging treatment, the temperature of the secondary aging treatment is 440° C., and the holding time is 5 hours, to obtain a finished strip.
[0057] Example 2
[0058] The composition of the copper alloy material for the automotive wiring harness terminal of this embodiment is shown in Table 1 and Table 2, and the performance test results are shown in Table 3, which are as follows:
[0059] S1. Prepare raw materials according to the composition of the copper alloy material for automobile wiring harness terminals, wherein the raw materials include: electrolytic copper, CuNi master alloy, CuP master alloy, CuMg master alloy, pure Zn, pure Sn and a first raw material, wherein the first raw material is selected from at least two of CuSi master alloy, CuCr master alloy, CuZr master alloy, CuMn master alloy and CuAg master alloy;
[0060] S2, melting and heat-insulating the electrolytic copper in a melting furnace, the melting temperature is 1200° C., the heat-insulating temperature is 1200° C., adding pure Zn, pure Sn and CuNi master alloy, CuP master alloy, CuMg master alloy and the first raw material in sequence, sampling and analyzing the qualified ones, and obtaining an intermediate solution;
[0061] S3, the intermediate solution is subjected to a second insulation, the second insulation temperature is 1180°C, the insulation time is 10min, and then the intermediate solution is subjected to a third insulation after the solution composition meets the requirements of the pulling column, the third insulation temperature is 1160°C, the insulation time is 5min, and then electromagnetic horizontal continuous casting is performed, the electromagnetic casting process is 25HZ frequency, 24A current, casting temperature is 1150°C, the drawing speed is 180mm / min, the pulling speed is 19mm / s, the pause time is 3s, and the withdrawal speed is 8mm / s to obtain a coil blank;
[0062] S4, homogenizing annealing the coiled blank at a temperature of 730°C and a holding time of 5 hours, then double-sided milling, and finally cold rough rolling with a thickness of 1.3 mm, and then solution treatment at a temperature of 900°C and a holding time of 2 minutes to obtain a solution quenched blank;
[0063] S5, subjecting the solution quenched billet to finish rolling deformation, with a finishing rolling deformation of 54%, and then subjecting it to primary aging treatment, with a primary aging temperature of 520° C. and a holding time of 5 h, to obtain a primary aging billet;
[0064] S6. The primary aging billet is subjected to finished product rolling, and the finished product rolling deformation is 47%, followed by secondary aging treatment, the temperature of the secondary aging treatment is 420° C., and the holding time is 6 hours to obtain a finished strip.
[0065] Example 3
[0066] The composition of the copper alloy material for the automotive wiring harness terminal of this embodiment is shown in Table 1 and Table 2, and the performance test results are shown in Table 3, which are as follows:
[0067] S1. Prepare raw materials according to the composition of the copper alloy material for automobile wiring harness terminals, wherein the raw materials include: electrolytic copper, CuNi master alloy, CuP master alloy, CuMg master alloy, pure Zn, pure Sn and a first raw material, wherein the first raw material is selected from at least two of CuSi master alloy, CuCr master alloy, CuZr master alloy, CuMn master alloy and CuAg master alloy;
[0068] S2, smelting and heat-insulating the electrolytic copper in a melting furnace, the smelting temperature is 1225° C., the heat-insulating temperature is 1210° C., pure Zn, pure Sn and CuNi master alloy, CuP master alloy, CuMg master alloy and the first raw material are added in sequence, sampling and analyzing the qualified products, and obtaining an intermediate solution;
[0069] S3, the intermediate solution is subjected to a second insulation, the second insulation temperature is 1190°C, the insulation time is 9 minutes, and then the intermediate solution is transferred to the insulation furnace through the submerged flow trough converter. After the solution composition meets the requirements of the pulling column, the third insulation is carried out, the third insulation temperature is 1170°C, the insulation time is 4 minutes, and then electromagnetic horizontal continuous casting is carried out. The electromagnetic casting process is 40HZ frequency, 30A current, casting temperature 1155°C, drawing speed 190mm / min, drawing speed 20mm / s, pause time 2s, and withdrawal speed 6mm / s to obtain a coil blank;
[0070] S4, homogenizing annealing the coiled blank at a temperature of 700°C and a holding time of 6 hours, then double-sided milling, and finally cold rough rolling with a thickness of 1.0 mm, and then solution treatment at a temperature of 890°C and a holding time of 4 minutes to obtain a solution quenched blank;
[0071] S5, subjecting the solution quenched billet to finish rolling deformation, with a finishing rolling deformation amount of 40%, and then subjecting it to primary aging treatment, with a primary aging temperature of 530° C. and a holding time of 4 h, to obtain a primary aging billet;
[0072] S6. The primary aging billet is subjected to finished product rolling, and the finished product rolling deformation is 55%, followed by secondary aging treatment, the temperature of the secondary aging treatment is 430° C., and the holding time is 5 hours, to obtain a finished strip.
[0073] Example 4
[0074] The composition of the copper alloy material for the automotive wiring harness terminal of this embodiment is shown in Table 1 and Table 2, and the performance test results are shown in Table 3, which are as follows:
[0075] S1. Prepare raw materials according to the composition of the copper alloy material for automobile wiring harness terminals, wherein the raw materials include: electrolytic copper, CuNi master alloy, CuP master alloy, CuMg master alloy, pure Zn, pure Sn and a first raw material, wherein the first raw material is selected from at least two of CuSi master alloy, CuCr master alloy, CuZr master alloy, CuMn master alloy and CuAg master alloy;
[0076] S2, smelting and heat-insulating the electrolytic copper in a melting furnace, the smelting temperature is 1240° C., the heat-insulating temperature is 1220° C., pure Zn, pure Sn and CuNi master alloy, CuP master alloy, CuMg master alloy and the first raw material are added in sequence, sampling and analyzing the qualified products, and obtaining an intermediate solution;
[0077] S3, the intermediate solution is subjected to a second insulation, the second insulation temperature is 1200°C, the insulation time is 8min, and then the intermediate solution is subjected to a third insulation after the solution composition meets the requirements of the pulling column, the third insulation temperature is 1180°C, the insulation time is 2min, and then electromagnetic horizontal continuous casting is performed, the electromagnetic casting process is a frequency of 20HZ, a current of 28A, a casting temperature of 1155°C, a drawing speed of 170mm / min, a drawing speed of 18mm / s, a pause time of 2s, and a withdrawal speed of 7mm / s, to obtain a coil blank;
[0078] S4, homogenizing annealing the coiled blank at a temperature of 750°C and a holding time of 4 hours, then double-sided milling, and finally cold rough rolling with a cold rough rolling thickness of 1.1 mm, and then solution treatment at a temperature of 885°C and a holding time of 3 minutes to obtain a solution quenched blank;
[0079] S5, subjecting the solution quenched billet to finish rolling deformation, with a finishing rolling deformation of 48%, and then subjecting it to primary aging treatment, with a primary aging temperature of 510° C. and a holding time of 5 h, to obtain a primary aging billet;
[0080] S6. The primary aging billet is subjected to finished product rolling, and the finished product rolling deformation is 52%, followed by secondary aging treatment, the temperature of the secondary aging treatment is 450° C., and the holding time is 4 hours to obtain a finished strip.
[0081] Example 5
[0082] The composition of the copper alloy material for the automotive wiring harness terminal of this embodiment is shown in Table 1 and Table 2, and the performance test results are shown in Table 3. The specific preparation steps are the same as those in Example 1.
[0083] Example 6
[0084] The composition of the copper alloy material for the automotive wiring harness terminal of this embodiment is shown in Table 1 and Table 2, and the performance test results are shown in Table 3. The specific preparation steps are the same as those of Example 1.
[0085] Example 7
[0086] The composition of the copper alloy material for the automotive wiring harness terminal of this embodiment is shown in Table 1 and Table 2, and the performance test results are shown in Table 3. The specific preparation steps are the same as those of Example 1.
[0087] Comparative Example 8
[0088] The composition of the copper alloy material for the automotive wiring harness terminal of this embodiment is shown in Table 1 and Table 2, and the performance test results are shown in Table 3. The specific preparation steps are the same as those of Example 1.
[0089] Example 9
[0090] The composition of the copper alloy material for automobile wiring harness terminals in this embodiment is the same as that in embodiment 1, except that the preparation steps are different, as follows:
[0091] S1. Prepare raw materials according to the composition of the copper alloy material for automobile wiring harness terminals, wherein the raw materials include: electrolytic copper, CuNi master alloy, CuP master alloy, CuMg master alloy, pure Zn, pure Sn and a first raw material, wherein the first raw material is selected from at least two of CuSi master alloy, CuCr master alloy, CuZr master alloy, CuMn master alloy and CuAg master alloy;
[0092] S2, melting and heat-insulating the electrolytic copper in a melting furnace, the melting temperature is 1200° C., the heat-insulating temperature is 1160° C., pure Zn, pure Sn and CuNi master alloy, CuP master alloy, CuMg master alloy and the first raw material are added in sequence, sampling and analyzing the qualified ones, and obtaining an intermediate solution;
[0093] S3, flowing the intermediate solution from the melting furnace into a casting mold for semi-continuous casting to obtain an ingot;
[0094] S4, heating the ingot to 950°C, keeping it at this temperature for 4 hours, and then hot rolling it to a thickness of 5 mm, and then homogenizing annealing it at 600°C, keeping it at this temperature for 2 hours;
[0095] S5, cold rolling the annealed material to a thickness of 1.2 mm, and then performing a solid solution treatment at 890°C for 3 minutes, followed by rapid cooling;
[0096] S5, finishing rolling the solutionized material with a deformation of 50%, and then performing an aging treatment at a temperature of 500°C for 6 hours to obtain a first-aging billet;
[0097] S6. The primary aging billet is subjected to finished product rolling, and the finished product rolling deformation is 45%, followed by secondary aging treatment, the temperature of the secondary aging treatment is 440° C., and the holding time is 5 hours, to obtain a finished strip.
[0098] Example 10
[0099] The composition of the copper alloy material for automobile wiring harness terminals in this embodiment is the same as that in embodiment 1, except that the preparation steps are different, as follows:
[0100] S1. Prepare raw materials according to the composition of the copper alloy material for automobile wiring harness terminals, wherein the raw materials include: electrolytic copper, CuNi master alloy, CuP master alloy, CuMg master alloy, pure Zn, pure Sn and a first raw material, wherein the first raw material is selected from at least two of CuSi master alloy, CuCr master alloy, CuZr master alloy, CuMn master alloy and CuAg master alloy;
[0101] S2, smelting and heat-insulating the electrolytic copper in a melting furnace, the smelting temperature is 1230° C., the heat-insulating temperature is 1215° C., pure Zn, pure Sn and CuNi master alloy, CuP master alloy, CuMg master alloy and the first raw material are added in sequence, sampling and analyzing the qualified products, and obtaining an intermediate solution;
[0102] S3, the intermediate solution is subjected to a second insulation, the second insulation temperature is 1195°C, the insulation time is 8min, and the intermediate solution is transferred to the insulation furnace through the submerged flow trough converter. After the solution composition meets the requirements of the pulling column, the third insulation is carried out, the third insulation temperature is 1175°C, the insulation time is 3min, and then electromagnetic horizontal continuous casting is carried out. The electromagnetic casting process is 30HZ frequency, 20A current, casting temperature 1160°C, drawing speed 150mm / min, drawing speed 14mm / s, pause time 1s, and withdrawal speed 4mm / s to obtain a coil blank;
[0103] S4, homogenizing annealing the coiled blank at a temperature of 800°C and a holding time of 5 hours, then double-sided milling, and finally cold rough rolling with a thickness of 1.5 mm, and then solution treatment at a temperature of 800°C and a holding time of 5 minutes to obtain a solution quenched blank;
[0104] S5, subjecting the solution quenched billet to finish rolling deformation, with a finishing rolling deformation of 60%, and then subjecting it to primary aging treatment, with a primary aging temperature of 500° C. and a holding time of 6 h, to obtain a primary aging billet;
[0105] S6. The primary aging billet is subjected to finished product rolling, and the finished product rolling deformation is 45%, followed by secondary aging treatment, the temperature of the secondary aging treatment is 440° C., and the holding time is 5 hours, to obtain a finished strip.
[0106] Embodiment 11
[0107] The composition of the copper alloy material for automobile wiring harness terminals in this embodiment is the same as that in embodiment 1, except that the preparation steps are different, as follows:
[0108] S1. Prepare raw materials according to the composition of the copper alloy material for automobile wiring harness terminals, wherein the raw materials include: electrolytic copper, CuNi master alloy, CuP master alloy, CuMg master alloy, pure Zn, pure Sn and a first raw material, wherein the first raw material is selected from at least two of CuSi master alloy, CuCr master alloy, CuZr master alloy, CuMn master alloy and CuAg master alloy;
[0109] S2, smelting and heat-insulating the electrolytic copper in a melting furnace, the smelting temperature is 1230° C., the heat-insulating temperature is 1215° C., pure Zn, pure Sn and CuNi master alloy, CuP master alloy, CuMg master alloy and the first raw material are added in sequence, sampling and analyzing the qualified products, and obtaining an intermediate solution;
[0110] S3, the intermediate solution is subjected to a second insulation, the second insulation temperature is 1195°C, the insulation time is 8min, and then the intermediate solution is subjected to a third insulation after the solution composition meets the requirements of the pulling column, the third insulation temperature is 1175°C, the insulation time is 3min, and then electromagnetic horizontal continuous casting is performed, the electromagnetic casting process is 30HZ frequency, 20A current, casting temperature is 1190°C, drawing speed is 200mm / min, drawing speed is 22mm / s, pause time is 3s, and withdrawal speed is 5mm / s, so as to obtain a coil blank;
[0111] S4, homogenizing annealing the coiled blank at a temperature of 800°C and a holding time of 5 hours, then double-sided milling, and finally cold rough rolling with a thickness of 1.5 mm, and then solution treatment at a temperature of 800°C and a holding time of 5 minutes to obtain a solution quenched blank;
[0112] S5, subjecting the solution quenched billet to finish rolling deformation, with a finishing rolling deformation of 60%, and then subjecting it to primary aging treatment, with a primary aging temperature of 500° C. and a holding time of 6 h, to obtain a primary aging billet;
[0113] S6. The primary aging billet is subjected to finished product rolling, and the finished product rolling deformation is 45%, followed by secondary aging treatment, the temperature of the secondary aging treatment is 440° C., and the holding time is 5 hours, to obtain a finished strip.
[0114] Comparative Example 1
[0115] The composition of the copper alloy material for automobile wiring harness terminals in this comparative example is shown in Tables 1 and 2, the performance test results are shown in Table 3, and the preparation steps are the same as those in Example 1.
[0116] Comparative Example 2
[0117] The composition of the copper alloy material for automobile wiring harness terminals in this comparative example is shown in Tables 1 and 2, the performance test results are shown in Table 3, and the preparation steps are the same as those in Example 1.
[0118] Comparative Example 3
[0119] The composition of the copper alloy material for automobile wiring harness terminals in this comparative example is shown in Tables 1 and 2, the performance test results are shown in Table 3, and the preparation steps are the same as those in Example 1.
[0120] Comparative Example 4
[0121] The composition of the copper alloy material for the automotive wiring harness terminal of this embodiment is shown in Table 1 and Table 2, and the performance test results are shown in Table 3. The specific preparation steps are the same as those of Example 1.
[0122] Table 1
[0123] Grouping Ni Sn P Zn Mg Example 1 0.5 2.2 0.3 0.3 0.02 Example 2 0.5 2.2 0.3 0.3 0.02 Example 3 0.5 2.2 0.3 0.3 0.02 Example 4 0.5 2.2 0.3 0.3 0.02 Example 5 0.7 1.8 0.2 0.5 0.018 Example 6 1 1.5 0.1 0.8 0.014 Example 7 1.2 1 0.01 0.1 0.01 Example 8 0.5 2.2 0.3 0.3 0.02 Example 9 0.5 2.2 0.3 0.3 0.02 Example 10 0.5 2.2 0.3 0.3 0.02 Embodiment 11 0.5 2.2 0.3 0.3 0.02 Comparative Example 1 0.5 2.2 0.3 0.3 0.02 Comparative Example 2 2.5 2.4 0.4 1 0.05 Comparative Example 3 0.2 0.6 0.005 0.05 0.005 Comparative Example 4 0.5 2.2 0.3 0.3 0.02
[0124] Table 2
[0125] Grouping Si Cr Zr Mn Ag Example 1 0 0.005 0.005 0 0 Example 2 0 0.005 0.005 0 0 Example 3 0 0.005 0.005 0 0 Example 4 0 0.005 0.005 0 0 Example 5 0.2 0.05 0.02 0.22 0.01 Example 6 0 0.005 0 0.005 0.005 Example 7 0.05 0.001 0.05 0.3 0.008 Example 8 0.02 0.07 0.003 0.002 0.02 Example 9 0 0.005 0.005 0 0 Example 10 0 0.005 0.005 0 0 Embodiment 11 0 0.005 0.005 0 0 Comparative Example 1 0 0 0 0 0 Comparative Example 2 0 0.005 0.005 0 0 Comparative Example 3 0 0.005 0.005 0 0 Comparative Example 4 0.3 0.003 0.06 0.4 0.004
[0126] Table 3
[0127]
[0128]
[0129] It can be seen from the above examples and comparative data that the copper alloy material for automotive wiring harness terminals provided by the present application has better and more balanced performance parameters, among which the grain size is smaller. Specifically, Examples 1 to 4 are copper alloy materials prepared under different preparation parameters and the same raw material ratio. Compared with the data of Example 10 and Example 11 and Comparative Example 1, they have higher tensile strength, elongation and conductivity, and smaller grain size. At the same time, compared with Example 9, Example 9 adopts a conventional semi-continuous casting process under the same element ratio. It can be clearly seen that the copper material obtained by the horizontal continuous casting process of the present application has better comprehensive performance. When using the element ratio within the preferred range of the present application, Examples 5 and 6 can still reach or even exceed the performance of the copper material obtained in Example 1. Compared with Comparative Examples 1-3, it can be clearly seen that the element ratio within the preferred range of the present application has an outstanding contribution to the copper alloy material of the present application to obtain good comprehensive performance. By comparing Example 1 with Examples 7-8 and Comparative Example 4, it can be seen that when the element dosage ratio of Si, Cr, Zr, Mn and Ag is not within the preferred range, it will significantly affect the comprehensive properties of the final copper alloy material, not only the tensile strength will be greatly reduced, but also the elongation, conductivity and other properties will have a more obvious decline.
[0130] At the same time, in the process of repeating the above-mentioned Example 1 and Example 10, the product yield of Example 1 is higher. Since semi-continuous casting is not a full-time continuous production, there are more pauses and start-up processes, resulting in lower production efficiency and a corresponding decrease in the yield.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A copper alloy material for automobile wiring harness terminals, characterized in that: Calculated by mass percentage as 100%, the copper alloy material includes: 0.5-1.2% Ni, 1-2.2% Sn, 0.01-0.3% P, 0.1-0.8% Zn, 0.01-0.02% Mg and 0.01-0.5% of at least two elements selected from Si, Cr, Zr, Mn and Ag, and the remainder is Cu and unavoidable impurities.
2. The copper alloy material for automobile wiring harness terminals according to claim 1, characterized in that: The Si content is 0.05-0.2%, and / or; the Cr content is 0.005-0.05%, and / or; the Zr content is 0.005-0.05%, and / or; the Mn content is 0.005-0.3%, and / or; the Ag content is 0.005-0.01%.
3. The method for preparing the copper alloy material for automobile wiring harness terminals according to claim 1 or 2, characterized in that: The steps include: Step 1, preparing raw materials according to the composition of the copper alloy material for automobile wiring harness terminals, the raw materials comprising: electrolytic copper, CuNi master alloy, CuP master alloy, CuMg master alloy, pure Zn, pure Sn and a first raw material, the first raw material being selected from at least two of CuSi master alloy, CuCr master alloy, CuZr master alloy, CuMn master alloy and CuAg master alloy; Step 2, smelting and heat-insulating the electrolytic copper in a melting furnace, and sequentially adding pure Zn, pure Sn, CuNi master alloy, CuP master alloy, CuMg master alloy and the first raw material to obtain an intermediate solution; Step 3: The intermediate solution is subjected to a second heat preservation, and then passed through a submerged flow trough converter to a heat preservation furnace. After the solution composition meets the casting requirements, the third heat preservation is carried out, and then electromagnetic horizontal continuous casting is carried out at a casting temperature of 1150-1160° C. to obtain a coil blank; Step 4: homogenizing annealing the coiled blank, then double-sided milling, and finally cold rough rolling with a cold rough rolling thickness of 1.0-1.5 mm, and then solution treatment to obtain a solution quenched blank; Step 5, subjecting the solution quenched billet to finish rolling deformation, with a finishing rolling deformation amount of 40-60%, and then subjecting the billet to an aging treatment to obtain a primary aging billet; Step 6: Roll the primary aging billet into finished product, and then perform secondary aging treatment to obtain a finished strip.
4. The method for preparing the copper alloy material for automobile wiring harness terminals according to claim 3, characterized in that: In step 2, the smelting temperature is 1220-1240°C and the holding temperature is 1200-1220°C.
5. The method for preparing the copper alloy material for automobile wiring harness terminals according to claim 3, characterized in that: In step three, the second insulation temperature is 1180-1200° C., and the insulation time is 8-10 min, and / or the third insulation temperature is 1160-1180° C., and the insulation time is 2-5 min.
6. The method for preparing the copper alloy material for automobile wiring harness terminals according to claim 3, characterized in that: In step three, the electromagnetic casting process has a frequency of 20-40 Hz and a current of 20-30A.
7. The method for preparing the copper alloy material for automobile wiring harness terminals according to claim 3, characterized in that: In step three, the process parameters of horizontal continuous casting are: casting speed is 160-190 mm / min, pulling speed is 16-20 mm / s, pause time is 1-3s, and withdrawal speed is 6-8 mm / s.
8. The method for preparing the copper alloy material for automobile wiring harness terminals according to claim 3, characterized in that: In step 4, the homogenization annealing temperature is 700-750°C, the holding time is 4-6h, the solution treatment temperature is 880-900°C, and the holding time is 2-5min.
9. The method for preparing the copper alloy material for automobile wiring harness terminals according to claim 3, characterized in that: In step five, the primary aging temperature is 500-530°C, and the holding time is 4-6h.
10. The method for preparing the copper alloy material for automobile wiring harness terminals according to claim 3, characterized in that: In step 5, the rolling deformation of the finished product is 45-55%, the temperature of the secondary aging treatment is 420-450° C., and the holding time is 4-6 hours.